Business Model Innovation Strategy To Increase Business Resilience In The Retail Sector In The Era Of Digital Disruption (Case Study In 2023) - Elsa Islammia Pasha (Al-Makki Publisher, 2023)
The global retail sector is undergoing a fundamental transformation due to digital disruption, which is changing consumer behavior and demanding adaptation of business models. Business resilience is critical in this era, where companies must be able to innovate to survive and grow. Business Model Innovation (BMI) is emerging as a key strategy to meet these challenges, especially in the context of increasingly complex competition post-pandemic. This study aims to identify the forms of BMI adopted by retail companies in 2023, analyze their contribution to business resilience, and formulate a BMI strategic framework to improve business resilience in the retail sector. The study used a qualitative approach with a holistic single case study design on one national retail company in Indonesia. Data is collected through in-depth interviews, observations, and document studies, thematically analyzed with the help of NVivo or Atlas.ti software. The implementation of BMI through the integration of omnichannel strategies, data-driven personalization, the development of multiple revenue streams, and the development of a digital ecosystem has been proven to increase business resilience. This innovation increases operational agility, customer engagement, and competitive advantage. BMI's strategy is effective in building retail business resilience in the digital era. The implication is that business actors need to integrate digital technology, agile business models, and a culture of innovation to achieve sustainable resilience.